Structural response analysis of conductive ethylene–propylene–diene monomer rubber composite pavement under validated temperature field. (18th April 2022) - Wei, Haibin; Ma, Zipeng; He, Xin; Han, Shuanye; Jiang, Boyu
Highlights: The EPDM pavement structural response under three different loading conditions were analyzed. Under the static load of the vehicle, the addition of EPDM composite material can reduce the cracking risk of the asphalt pavement. The temperature load caused by the active heating of the road surface is the main factor causing the damage of the EPDM pavement. The weakest part of the entire pavement structure is the lower asphalt layer close to the composite material, especially at the center of the wheel load action spacing. Abstract: Conductive ethylene–propylene–diene monomer rubber composite material (EPDM) is a new type of active electric heating deicing material. It has good heat generation and mechanical properties. In this study, in order to study the effect of the addition of EPDM on the response of the pavement structure, the composite material was laid under the asphalt layer in the pavement structure in a full-width paving method. A three-dimensional finite element model of EPDM pavement structure was established and the pavement heating temperature field was simulated. The simulated temperature field of road surface was verified by an outdoor heating test. The structural response of EPDM pavement under three different loading conditions was analyzed by using the ANSYS static structural analysis module. The structure response was analyzed from three indicators of bottom tensile stress, surface deformation, and equivalent stress. The results show that under the static load of the vehicle, the addition of EPDM composite material can reduce the cracking risk of the asphalt pavement; The temperature load caused by the active heating of the road surface is the main factor causing the damage of the EPDM road surface; The weakest part of the entire pavement structure is the lower asphalt layer close to the composite material, especially at the center of the wheel load action spacing. This study can provide a reference for future practical engineering applications of EPDM pavements and attract attention to the effect of temperature loads generated by active snow-melting pavement heating on the structural response of the pavement.